Debajo de sus Faldas . Under Their Skirts - Maria Suez, Esteban Varade (Nananino, 2008)
Verzio FF Submission Female genital mutilation is a traditional practice in several countries. In most cases FGM is connected to the preservation of traditional views and values. Some believe that it preserves beauty, brings honor, imporves marriage prospects, social status and chastity of the girls. The practice however is highly dangerous, causes severe pain, can provoke prolonged bleeding, infection, infertility and even death. Many girls and women suffer in silence. This film wants to break the silence and shed light upon the dangers of such practices and raise awareness.